Spatial Efficiency and Site Optimization Analysis of a Vertical Educational Facility in Pekanbaru - Haryani; Kusumah, Dadang Puja; Tela, I Nengah (Journal of Architectural Research and Design Studies, 2025)
This study examines the spatial efficiency and sustainable site development of the Poltekkes Riau Tower, a vertical educational facility, using the Greenship New Building Version 1.2 framework established by the Green Building Council Indonesia (GBCI). It focuses on the Appropriate Site Development (ASD) category and assesses green area ratio, site selection, accessibility, transportation, landscape quality, microclimate control, and stormwater management. The building scored 5 out of 17 points (29.4%), indicating shortcomings in bicycle access, landscaping, and runoff mitigation. The evaluation process involves four key steps: (1) Scoring Analysis, which quantifies compliance with the Greenship criteria; (2) Spatial Mapping of green cover, access, and hydrology based on site plans and field data; (3) Gap Identification, which compares actual conditions with benchmarks; and (4) Recommendation Formulation to enhance sustainability through passive design, landscape optimization, and integrated stormwater systems. The findings provide insights for improving site sustainability in future vertical educational buildings located in tropical urban settings.